Authorship in the eighteenth century - Rounce, Adam (Oxford University Press, 2015)
This essay looks at different questions facing authorship in the eighteenth century, from the widespread use of anonymity, and its consequences; the perception of an over-abundance of authors, and the related fear of a massive cultural decline; the ways in which an authorial canon could have been more arbitrary and less comprehensive than a modern day equivalent; the manner in which poetic representations of authorship sought to compete with, and pre-empt other criticisms and versions of the self; the extensive use of self-reflexivity in fiction, intended to guide and misguide the reader; and the consequences of the growing interest in authorship as a reflection of personality and celebrity.